2019
DOI: 10.3390/jcm8010079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cholecystectomy on the Gut Microbiota: A Case-Control Study

Abstract: Cholecystectomy alters the bile flow into the intestine and the enterohepatic circulation of the bile acids; this may affect the gut microbiota. We assessed the gut microbiota composition of patients who had undergone cholecystectomy and compared with those who had not. From a cohort of 1463 adult participants who underwent comprehensive health screening examinations, 27 subjects who had undergone cholecystectomy (cholecystectomy group) and 81 age- and sex-matched subjects who had not (control group) were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 48 publications
2
50
1
Order By: Relevance
“…Second, cholecystectomy can increase the risk of CRC by enhancing the risk of the metabolic syndrome due to the impairment of cholesterol metabolism [26,34,35]. Third, cholecystectomy can change the activity of colonic microbiota, which can also lead to the development of CRC [36,37]. However, our study does not demonstrate the detrimental effect of cholecystectomy on the development of CRC, therefore, these explanations above hardly support our findings.…”
Section: Discussioncontrasting
confidence: 72%
“…Second, cholecystectomy can increase the risk of CRC by enhancing the risk of the metabolic syndrome due to the impairment of cholesterol metabolism [26,34,35]. Third, cholecystectomy can change the activity of colonic microbiota, which can also lead to the development of CRC [36,37]. However, our study does not demonstrate the detrimental effect of cholecystectomy on the development of CRC, therefore, these explanations above hardly support our findings.…”
Section: Discussioncontrasting
confidence: 72%
“…Cholecystectomy leads to a significant change in the composition of the gut microbiota [ 9 , 12 ]. After cholecystectomy, an even more pronounced decrease in the actual number of taxa occurs compared with individuals without GSD [ 9 , 11 ] and an increase in the number of Bifidobacterium and Anaerostipes Dorea [ 11 ]. In some individuals, an increase in the species B. obeum and V. Parvula (type Firmicutes ) [ 9 , 11 ] and Bacteroidetes [ 13 ] is noted.…”
Section: Gut Microbiome and Cholecystectomymentioning
confidence: 99%
“…In 1966, Maki [ 6 ] showed the role of bacterial infection in the pathogenesis of pigmented gallstones. Later, in several works, it was demonstrated that changes in the gut microbiota are also one of the etiological factors of cholesterol gallstones [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in China found that gut bacterial composition in healthy people changed with age, but the change was lost in PC patients, and the abundance of Bacteroidetes decreased in PC patients ( 18 ). Additionally, another study which contained 27 PC patients showed a subtle difference in the diversity of gut microbiota between the cholecystectomy and control groups ( 19 ). Nevertheless, these previous results were controversial, and the characterization in gut microbiota after cholecystectomy is still unclear.…”
Section: Introductionmentioning
confidence: 99%